A Legal Perspective on the Cooperation Agreement in Cash on Delivery (COD) System - Faradini, Nurul; Thalib, Mutia Cherawaty; Sarson, Mohamad Taufiq Zulfikar (Damhil Law Journal, 2023)
The purpose of this research is the Cooperation Agreement between the Goods Delivery Service Company and the Courier in the Cash on Delivery System. This research uses empirical research method. The research location is Ninja Xpress Gorontalo City. The data obtained are primary and secondary data. Data collection techniques used by the author are observation, interviews and literature. The research results obtained Every agreement must be carried out in good faith, as found in Article 1338 Paragraph (3) of the Civil Code regarding the principle of good faith, which reads â€œAgreements must be carried out in good faithâ€. This article determines that agreements are made in good faith by those who make them. The most important thing in the implementation of an agreement is to determine when the agreement begins, considering that from that moment the rights and obligations of the parties to the agreement arise. In general, an agreement occurs after an agreement between the parties, since there is an agreement, then from that moment an obligation has arisen. In addition, the contents of the agreement between Ninja Xpress and couriers consist of the scope of the agreement, validity period & termination of the agreement, agreement of the parties, work compensation, dispute resolution, tiering system, COD scheme, awards or awards for the best rider/driver and sanctions for violation of procedures. The form of agreement between the courier and Ninja Express is a partnership agreement which can be in the form of a digital agreement or print out agreement.